2020
DOI: 10.1515/jbcpp-2019-0227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endogenous sulfur dioxide on spatial learning and memory and hippocampal damages in the experimental model of chronic cerebral hypoperfusion

Abstract: BackgroundThe vascular changes due to cerebrovascular damage, especially on the capillaries, play a vital role in causing vascular dementia. Increasing oxidative stress can lead to tissue damage while reducing brain blood flow. The use of factors reducing the oxidative stress level can decrease the brain damages. Sulfur dioxide (SO2) is one of the most important air pollutants that lead to the development of severe brain damage in large quantities. However, studies have recently confirmed the protective effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Chronic cerebral hypoperfusion is a pathological state involved in the generation of dementia. Consistent with the previous study (Choi et al, 2016), spatial learning and memory impairment testing by the Morris water maze is observed in our model of CCH (Ghasemi et al, 2020). We proved for the first time that Fructus Broussonetiae could improve long-term memory revealed by increased frequency of platform crossing and shortened escape latency time.…”
Section: Discussionsupporting
confidence: 92%
“…Chronic cerebral hypoperfusion is a pathological state involved in the generation of dementia. Consistent with the previous study (Choi et al, 2016), spatial learning and memory impairment testing by the Morris water maze is observed in our model of CCH (Ghasemi et al, 2020). We proved for the first time that Fructus Broussonetiae could improve long-term memory revealed by increased frequency of platform crossing and shortened escape latency time.…”
Section: Discussionsupporting
confidence: 92%
“…Other experiments demonstrated that the selective alpha-7-nicotinic AChR antagonism exacerbates the hypoxic effects on the CA1 and CA3 cortical areas; on the contrary, non-selective nicotinic AChR antagonists have a detrimental effect on the hippocampus, not in all the other cortical areas [158][159][160][161]. The chronic reduction of the cerebral blood flow can affect the control of the cholinergic networks, but it happens that a proper cholinergic function is compulsory to well-regulation of the regional brain blood flow [162,163]. Ach principally mediates the parasympathetic innervation of the Willis circle and the pial vessels [164].…”
Section: Cholinergic Role In Small Vessel Diseasementioning
confidence: 99%
“…Another study found that the combined effect of SO 2 and PM 2.5 led to the accumulation of Aβ in the cerebral cortex and hippocampus of rats ( 28 ). However, other studies have found that SO 2 may alleviate the injury caused by chronic cerebral hypoperfusion by enhancing the antioxidant capacity of the hippocampus ( 29 ). In addition, it has been reported that low doses of PM 2.5 and SO 2 coexposure can lead to neurodegenerative changes, including neuronal apoptosis and reductions in synaptic structural and functional proteins ( 30 ).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%